Hiperrealitas Simulakra Pengguna Instagram Mahasiswa Fakultas Ushuluddin Adab Dan Dakwah IAIN Parepare - Siti Jamilah; Suhardi; Nurhalizah, Siti Nurhalizah (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
Simulacra hyperreality is a picture of the collapse of realities that are taken over by engineering models (images, hallucinations, simulations) which are considered more real than reality itself so that the difference between the two becomes blurred as constructions in the media. the simulacra hyperreality of instagram users and what factors influence the hyperreality behavior of instagram users. Students of the Faculty of Ushuluddin Adab and Da'wah IAIN Parepare. This research use desciptive qualitative approach. A qualitative approach is a research that produces descriptive data in the form of written or spoken words of people, and observable behavior. The technique used is in the form of observation and documentation data collection techniques. Observation of hyperreality posts.The results of this study indicate that the form of simulacra hyperreality of Instagram users of Ushuluddin, Adab and Da'wah Faculty of IAIN Parepare students includes, students reflecting on basic reality (simulation), covering and distorting basic reality (simulacra), covering up the absence of basic reality (hyperreality), and showing the disappearance of relationships. with any reality and what is shown. The results of further research are the factors that influence the occurrence of hyperreality in the form of followers, engagements, and content variations.